The Impact of Covid-19 on Liquidity and Profitability in the Hotel Industry - Siti Sheila Miranda Tri utami; Endah Dewi Purnamasari; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the impact of Covid-19 on liquidity and profitability in the Hospitality Industry. This study utilized secondary data. The source of the data used in this study was obtained from the Hospitality Industry quarterly financial report data. The sample in this study was 9 Hospitality Industry companies listed on the Indonesia Stock Exchange (IDX). The method of analysis in this study was Vertical Analysis and Horizontal Analysis. The results show that the Covid-19 pandemic has an impact on liquidity and profitability in the Hospitality Industry in Indonesia. This research is expected to be useful for companies to determine and maintain the Liquidity and Profitability of the Hospitality Industry during the Covid-19 pandemic